Sejarah SMP Al-Azhar Mandiri Palu 1992-2022 - Mohammad Fadel; Haliadi Haliadi; Suyuti Suyuti; Nuraedah Nuraedah; Misna Misna (Journal on Education, 2024)
This research aims to solve problems regarding (1) Describing the history of the founding of Al-Azhar Mandiri Middle School Palu, (2) Outlining the carrying capacity of historical values ​​of "kealazharan" as the basis of education at Al-Azhar Mandiri Middle School Palu, and (3) Analyzing policies regarding the cultural rules of etiquette and school social life rules at Al-Azhar Mandiri Middle School, Palu. This research is qualitative research that uses a historical approach. The research subjects were the Director of the Al-Azhar Foundation as the founder, teachers/staff and former teachers, as well as several alumni students from Al-Azhar Mandiri Middle School, Palu. The type of data used in this research is qualitative research, with data collection methods based on documents, archives, interviews, direct observation, observations and other supporting physical devices. The research results obtained are (1) The history of the founding of Al-Azhar Mandiri Pau Middle School is a form of thought by Abdul Basit Arsyad which was initiated by his own father, namely KH. Rustam Arsyad in creating the Al-Azhar Diniyah study park, after which it changed to Al-Azhar Ibtidayah Madrasah, until now it has become a formal education with the name Al-Azhar Mandiri Palu Middle School; (2) The carrying capacity of historical values ​​of "kealazharan" as the basis of education at Al-Azhar Mandiri Palu Middle School is marked by the basic thoughts of KH's ancestors. Rustam Arsyad who continues to adhere to scientific principles held as a form of thought by a figure named Said Idrus bin Salim Aljufri (or known as the Old Teacher) in building schools; (3) The policy regarding the cultural regulations for etiquette and school social life rules at Al-Azhar Mandiri Middle School in Palu is contained in a policy made in the form of rules which are intended as signs for students (i) to submit and pronounce their behavior, sayings and act in order to create a school climate and culture that can support effective learning activities, both within the school environment and outside the school